Uso del mucilago de cacao en el control de maleza en plantaciones comerciales de cacao (Theobroma cacao L.) - García Navarrete, Maikel David (2022)
Cocoa mucilage is a viable alternative that should be taken into consideration by cocoa producers for weed control, because it tends to develop much less resistance in weeds than chemical products (herbicides). Cocoa mucilage is selective to certain weed species and has a rapid degradation that can be favorable, as it reduces the possibility of residues remaining in food, soil and ecosystems, as well as having a unique movement. The use of mucilage in a weed management program in cocoa cultivation has two benefits: in the short term, its inhibitory effect reduces the herbicide application cycles or labor; the second benefit is in the long term, since it reduces the flowering of some weed species such as Rottboelia cochinchinensis, and therefore the generation of seeds is lower in the field. The information obtained was carried out through the technique of analysis, synthesis and summary, with the purpose of informing the reader about the use of cocoa mucilage in the control of weeds in commercial cocoa plantations (Theobroma cacao L.). Based on the above, it was determined that cocoa mucilage can be used as a control tool by affecting the synthesis of proteins in weeds and changing their conformation, due to its inhibitory priority of some enzymatic actions in the metabolism of plants. The basis of the inhibitory effect is due to its composition: alkaloids, tannins, flavonoids and steroids. Cocoa mucilage presents a variation of control and act quickly, but its management requires permanence and more established efficacy studies. Cocoa mucilage has a rapid degradation that can be favorable, as it reduces the possibility of residues remaining in food, soil and ecosystems, as well as having a unique movement and being biodegradable.